Pros and Cons of Goods and Service Tax (GST) on Indian Economy (International Journal of Emerging Trends in Science and Technology, 2017)
GST the biggest reform in indian system of taxation was applied all over the country since 1st july ,2017.It is a unified system of taxation. Now with GST like most of the other countries of the world ,our countryalso has a world class tax structure. The motive of GST is to remove the multiple taxes that are leived onthe goods and services and replace it with one single tax , gst. There will be many reforms in differentsectors of the economy after the implementation of gst .The present paper is an attempt to know the prosand cons of gst on the economy